Identifying critical parameters for extraction of carnosine and anserine from chicken meat with high voltage pulsed electric fields and water. (March 2022) - Robin, Arthur; Ghosh, Supratim; Gabay, Batel; Levkov, Klimentiy; Golberg, Alexander
Abstract: Carnosine (β-alanyl-L-histidine) and its methylated counterpart anserine (β-alanyl-1-methylhistidine) are important functional dipeptides found in various vertebrates' tissues. In this study, we identified the critical parameters of pulsed electric fields (PEF), coupled to mechanical pressing, followed by incubation in water up to 240 min for the extraction of these bioactive dipeptides from chicken meat. We show that PEF improves the kinetics of anserine and carnosine release to water by 7 to 53%, compared to the same water extraction process without PEF when the incubation time is below 120 min. A fractional factorial design showed that the incubation time in the water, after PEF pretreatment, had the most significant effect on dipeptides extraction. The maximum achieved total protein yield was 15.5 mg gfresh weight(FW) -1 after 120 min incubation in water. The maximum carnosine extraction yield was 7.48 mg gFW −1 with a maximum anserine extraction yield of 3.05 mg gFW −1 . The specific energy yield of extraction of protein, carnosine, and anserine was 488.16 mg J −1, 39.43 mg J −1, and 131.63 mg J −1 respectively. The developed method is scalable and could be further explored to extract bioactive compounds from animal tissues. Highlights: Extraction of functional dipeptides from chicken meat by inducing electroporation. Pulsed electric field treatments could enhance extraction yields of carnosine and anserine. Study on the impact of process parameters revealed crucial factors to consider. Potential for value-addition from animal tissues by low-energy scalable PEF technology